2013
DOI: 10.2175/106143013x13596524515780
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxic Effects of Chloramphenicol on Scenedesmus Obliquus and Chlorella Pyrenoidosa

Abstract: The acute and chronic toxicological effects of Chloramphenicol (CAP) on Scenedesmus obliquus and Chlorella pyrenoidosa are not well understood. The indoor experiments were carried to observe and analyze the CAP induced changes. Results of the observations have showed that CAP exposure could significantly inhibit the growth of Scenedesmus obliquus in almost all the treated groups, while Chlorella pyrenoidosa exhibited less sensitivity. Chlorophyll-a syntheses of Scenedesmus obliquus were all inhibited by CAP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…Moreover, increases in CAT activities are also considered adaptive traits against the damage caused by oxidative stress (Rasheed and Mukerji, ). The study conducted by Zhang et al (,b) also indicated that CAT activity in S. obliquus and Chlorella pyrenoidosa was significantly increased compared with controls after exposure to chloramphenicol (5–100 mg/L), which is in line with our results showing that ≥100 mg/L chloramphenicol dramatically increased CAT activity in D. magna .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, increases in CAT activities are also considered adaptive traits against the damage caused by oxidative stress (Rasheed and Mukerji, ). The study conducted by Zhang et al (,b) also indicated that CAT activity in S. obliquus and Chlorella pyrenoidosa was significantly increased compared with controls after exposure to chloramphenicol (5–100 mg/L), which is in line with our results showing that ≥100 mg/L chloramphenicol dramatically increased CAT activity in D. magna .…”
Section: Discussionsupporting
confidence: 93%
“…Assays were carried out in 100‐mL glass beakers with 50 mL of the test medium, and each test concentration had 10 replicates with one neonate each. The medium was renewed daily; the neonates were fed every day during the 21‐d exposure with a regime of 3 × 10 5 cell/mL S. obliquus (Zhang et al ,b). The dissolved oxygen, pH, and temperature were measured before and after each renewal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used in aquaculture and animal‐farming industries because of its broad‐spectrum antimicrobial activity (Lu et al, 2009). Exposure to CAP can trigger severe allergic reactions, especially aplastic anemia (Zhang et al, 2013; Tan et al, 2017; US National Library of Medicine, 2017). Its use is now prohibited in many countries because of its adverse effects on human health (Nicolich et al, 2006).…”
mentioning
confidence: 99%